Reperfusion syndrome in carotid artery surgery - Samarsky, Igor (Journal of Education, Health and Sport, 2015)
Samarsky Igor. Reperfusion syndrome in carotid artery surgery. Journal of Education, Health and Sport. 2015;5(8):219-225. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.28075 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A219-225 https://pbn.nauka.gov.pl/works/671236 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.06.2015. Revised 15.07.2015. Accepted: 12.08.2015. Reperfusion syndrome in carotid artery surgery Samarsky Igor Military Medical Clinical Centre of South region, Odesa, Ukraine ABSTRACT Reperfusion syndrome in carotid artery surgery. Samarsky Igor Military Medical Clinical Centre of South region, Odesa, Ukraine The study was aimed to evaluate the frequency of reperfusion injury after carotid artery surgery. It was found that reperfusion syndrome appeared in 27,9% patients when intraoperative administration of creatine phosphate was not applied. The use of intraoperative neuroprotection cut the frequency of reperfusion injury syndrome to 3.4% cases. The feasibility of intraoperative administration of creatine phosphate could improve the results of the surgical treatment of patients with stenotic lesions of carotid arteries is discussed. Key words: carotid artery, reperfusion injury, surgery, treatment, prevention.